Evaluación de la efectividad de herbicidas post-emergentes en control de malezas empleando diferentes dosificaciones y mezclas en el cultivo de maíz - Cevallos López , Bryan Roy (2023)
Weeds decrease the productivity of the corn crop, by competing for the nutrients found in the soil, being these hosts of insects and pathogens, in addition, the incorrect use of the application of herbicides in the increase of extreme doses and the inadequate herbicide influences directly in the deterioration of soils, leaving them sterile and infertile, altering their ecosystem to the point of contaminating groundwater. The main objective of the research is to evaluate the effectiveness of post-emergent herbicides in weed control using different dosages and mixtures in the corn crop, a completely randomized block design (DCBA) was implemented, with 10 treatments in which includes an absolute control with 4 repetitions, the analysis of variance (ANOVA) was performed and to compare the means, Duncan's test at 95% was used. These data will be analyzed by InfoStat v.2020. The hybrid ADVANTA 9139 was used as plant material. Different herbicides were applied at different dosages, in order to determine the effect on weeds present in corn crops at 15 and 38 days after the application of the herbicide and also its influence on maize plants. As a result, a greater influence was determined by controlling treatment 2 [Basta + Heat (Dose: 1 L+ 50g)], treatment 3 [Basta + Heat (Dose: 1.5 L + 50g)], treatment 4 [Gramoxone + Heat ( Dose: 2.0 L+ 0.50g)], treatment 9 [Gramoxone (Dose: 2.0 L)]; considering weed control as the best mixtures and doses. Concluding that the adequate selection of herbicides to combat the host weeds in the soil and the correct use of doses eradicates the presence of weeds in the corn crop, in turn improving the health status of the plant, obtaining a profitable production. Keywords: Weeds, herbicides, productivity